CULTURAL AND LINGUISTIC FOUNDATIONS FOR ACHIEVING EQUIVALENCE IN TRANSLATING DOCUMENTS OF INTERNATIONAL FINANCIAL ORGANIZATIONS - MOVLANOVA, Rano (The Lingua Spectrum, 2025)
Translation of financial and legal documents produced by international financial organizations (such as the IMF, World Bank, and OECD) requires not only linguistic precision but also cultural and conceptual equivalence. This article explores the challenges translators face in maintaining the semantic and pragmatic equivalence of financial terminology across languages and cultures. By analyzing examples from the translation of reports, financial statements, and regulatory texts, the study highlights how cultural frameworks shape interpretation, terminology choice, and legal meaning. The paper emphasizes that effective translation in international finance demands both cross-cultural competence and contextual awareness of global financial practices.